Causal Mechanisms in the Global Development of Social Policies - Kuhlmann, Johanna; Nullmeier, Frank (Global Dynamics of Social Policy, 2022)
This open access edited volume introduces the concept of causal mechanisms to explore new ways of explaining the global dynamics of social policy, and shows that a mechanism-based approach provides several advantages over established approaches for studying social policy. The introductory chapter outlines the mechanism-based approach, which stands out by modularisation and a clear focus on actors. The mechanism-based approach then guides the twelve chapters on social policy developments in different Asian, African, European and Latin American countries. Based on these findings, the concluding chapter provides a structured compilation of causal mechanisms and outlines how a mechanism-based approach can further strengthen research on the global development of social policies, especially in a comparative perspective. The edited volume is highly relevant for social policy scholars from a variety of disciplines, as well as for scholars interested in strengthening explanation in the social sciences.